Kesepuluh Orang Kusta (Lukas 17:11-19) dari Perspektif Penyintas Hiv di Maumere- Flores - Servinus Haryanto Nahak; Gabriel Galus; Yohanes Nepa; Krispianus Wedho; Fransiskus Sempo (Faculty of Theology Duta Wacana Christian University, 2023)
AbstractThis paper aims to analyze the text of Luke 17:11-19 about the ten lepers from the perspective of People Living with HIV/AIDS (PLWHA) in Maumere. The author conducts this research by using qualitative method. The data is taken from depth interviews and participatory observation at Flores Plus Support-Maumere Peer Support Group (KDS). By using a reader-oriented approach, this paper analyzed the experiences of PLWHA and their perspectives on the account of the ten lepers. Thefindings showed that for HIV survivors in Maumere, peer groups play an important role in raising their hopes in the midst of high rate of stigma and discrimination. In the eyes of PLWHA, the role of KDS can be juxtaposed with the “group” of the ten lepers in Luke’s story. AbstrakArtikel ini bertujuan untuk menganalisis teks Lukas 17:11-19 tentang kesepuluh orang kusta dari perspektif Orang dengan HIV/AIDS (ODHA) di Maumere. Untuk membahas masalah ini penulis melakukan penelitian kualitatif dengan wawancara mendalam dan observasi partisipatoris di Kelompok Dukungan Sebaya (KDS) Flores Plus Support-Maumere. Dengan menggunakan pendekatan reader oriented artikel ini menganalisis pengalaman para ODHA dan sudut pandang mereka tentang kisahkesepuluh orang kusta. Hasil penelitian ini menunjukkan bahwa, bagi para ODHA di Maumere, kelompok sebaya memainkan peran penting untuk membangkitkan harapan mereka di tengah tingginya stigma dan diskriminasi. Dalam kacamata para ODHA, peran KDS dapat dibandingkan dengan “paguyuban” sepuluh orang kusta dalam kisah Lukas.